Multicentre evaluation of magnetic resonance imaging supported transperineal prostate biopsy in biopsy-naïve men with suspicion of prostate cancer - Hansen, Nienke Lynn; Kesch, Claudia; Bonekamp, David; Distler, Florian A.; Hadaschik, Boris (BJU international, 2018)
Objectives To analyse the detection rates of primary magnetic resonance imaging (MRI)-fusion transperineal prostate biopsy using combined targeted and systematic core distribution in three tertiary referral centres. Patients and Methods In this multicentre, prospective outcome study, 807 consecutive biopsy-naïve patients underwent MRI-guided transperineal prostate biopsy, as the first diagnostic intervention, between 10/2012 and 05/2016. MRI was reported following the Prostate Imaging-Reporting and Data System (PI-RADS) criteria. In all, 236 patients had 18-24 systematic transperineal biopsies only, and 571 patients underwent additional targeted biopsies either by MRI-fusion or cognitive targeting if PI-RADS ≥3 lesions were present. Detection rates for any and Gleason score 7-10 cancer in targeted and overall biopsy were calculated and predictive values were calculated for different PI-RADS and PSA density (PSAD) groups. Results Cancer was detected in 68% of the patients (546/807) and Gleason score 7-10 cancer in 49% (392/807). The negative predictive value of 236 PI-RADS 1-2 MRI in combination with PSAD of <0.1 ng/mL/mL for Gleason score 7-10 was 0.91 (95% confidence interval ± 0.07, 8% of study population). In 418 patients with PI-RADS 4-5 lesions using targeted plus systematic biopsies, the cancer detection rate of Gleason score 7-10 was significantly higher at 71% vs 59% and 61% with either approach alone (P < 0.001). For 153 PI-RADS 3 lesions, the detection rate was 31% with no significant difference to systematic biopsies with 27% (P > 0.05). Limitations include variability of multiparametric MRI (mpMRI) reading and Gleason grading. Conclusion MRI-based transperineal biopsy performed at high-volume tertiary care centres with a significant experience of prostate mpMRI and image-guided targeted biopsies yielded high detection rates of Gleason score 7-10 cancer. Prostate biopsies may not be needed for men with low PSAD and an unsuspicious MRI. In patients with high probability lesions, combined targeted and systematic biopsies are recommended.
Published online: 11 October 2017
Gesehen am 26.07.2018